Evaluasi Pengamanan Aset Tetap Tanah Dalam Rangka Menciptakan Pengelolaan Barang Milik Daerah Yang Tertib (Studi Kasus BKAD Kota Bogor) - Frestiawan, Salman; Muhammad, Rahma Nazila (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to evaluate security activities and find obstacles that become obstacles in the process of securing land fixed assets at the Regional Finance and Assets Agency (BKAD) of Bogor City. This evaluation process uses qualitative research methods with a descriptive approach. Based on the Regulation of the Mayor of Bogor City No. 114 of 2020 concerning the implementing regulations for the management of regional property, criteria have been established as a reference in security evaluation activities. The data obtained has been analysed using the Champion method. The results showed that the security of land assets carried out by BKAD Bogor City was in accordance with Perwali Kota Bogor No.114 of 2020 Articles 102-105, however, only administrative security had an impact on all land assets. Then there are still obstacles in the process of securing land assets that come from external and internal BKAD, these obstacles are related to the competence of human resources (HR), communication and coordination with external parties, disputes, digitalisation of assets, and human error. The benefits of this research are as evaluation material for BKAD Bogor City to consider the results of recommendations in the process of securing land fixed assets, and this research is expected to be a source of reference for the development of science.